2016
DOI: 10.1242/jcs.175307
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Vb mediates Cu+ export in polarized hepatocytes

Abstract: The cellular machinery responsible for Cu + -stimulated delivery of the Wilson-disease-associated protein ATP7B to the apical domain of hepatocytes is poorly understood. We demonstrate that myosin Vb regulates the Cu + -stimulated delivery of ATP7B to the apical domain of polarized hepatic cells, and that disruption of the ATP7B-myosin Vb interaction reduces the apical surface expression of ATP7B. Overexpression of the myosin Vb tail, which competes for binding of subapical cargos to myosin Vb bound to subapic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…After 3 h, MAL2 surface labeling was lost with increased staining observed in the apical compartment, a structure that labels exclusively for apical membrane proteins in nonpolarized cells as we and other have previously extensively described ( Figure 5B(c)) [26]. After 4 h, labeling at the "apical compartment" and cell surface were observed consistent with the recycling reported for apical residents between these two compartments in nonpolarized cells also as we have previously described ( Figure 5B(d)) [26][27][28].…”
Section: Mal2 Expression In Clone 9 Cells Induced Protrusion Formatiosupporting
confidence: 87%
“…After 3 h, MAL2 surface labeling was lost with increased staining observed in the apical compartment, a structure that labels exclusively for apical membrane proteins in nonpolarized cells as we and other have previously extensively described ( Figure 5B(c)) [26]. After 4 h, labeling at the "apical compartment" and cell surface were observed consistent with the recycling reported for apical residents between these two compartments in nonpolarized cells also as we have previously described ( Figure 5B(d)) [26][27][28].…”
Section: Mal2 Expression In Clone 9 Cells Induced Protrusion Formatiosupporting
confidence: 87%
“…Another molecular player has been recently reported to drive apical targeting of ATP7B. Myosin Vb has been demonstrated to participate in the delivery of ATP7B to the apical domain of polarized hepatic cells exposed to Cu, while disruption of the ATP7B/myosin Vb interaction significantly impaired apical expression of ATP7B . Thus, the apical delivery of ATP7B might be coordinated by p62/DNCT4 and myosin Vb motors by moving ATP7B‐containing organelles along microtubules and actin filaments, respectively .…”
Section: Final Destination Of Atp7bmentioning
confidence: 99%
“…One of the answers is that F-actin regulates the expression and function of membrane transporters involved in cisplatin transport. The previous reports demonstrated that the rearrangement of F-actin increased the expression of cisplatin importer CTR1 (Abdellatef et al, 2015) and that the translocation of cisplatin exporters, ABC7A and ABC7B, from the trans-Golgi network to the plasma membrane is regulated by the formation of F-actin (Cobbold et al, 2002;Gupta et al, 2016). It is well known that the actin cytoskeleton regulates the VSOR anion channels, which contributes to cisplatin influx and sustained cell shrinkage during early apoptosis.…”
Section: The Role Of the Actin Cytoskeleton In Cisplatin-induced Apopmentioning
confidence: 97%